Diversidad genética del Ovino Criollo de Pelo Colombiano mediante el uso del marcador molecular de tipo polimorfismos de nucleótido simple (SNP) - Ortiz Sanchéz, Yurany (2021)
The aim of this study was to genetically characterize the population of the Colombian Creole Hair Sheep (CCHS) from two geographical areas of the country, the Piedemonte Llanero (PDML) and the Interandine Valleys of the Magdalena River (VIRM). Muscle samples were taken and DNA was extracted using the phenol chloroform isoamyl methodology. Genotyping was done with the OvineSNP50 BeadChip Data Sheet. The genotypes were analysed with the PLINK v.1.9 software for relationships of consanguinity and kinship. Statistical analyses of the data were performed using the “genepop” and “adegenet” packages of the R software. The results showed an expected heterozygosity of 0.374 for the CCHS, while it was 0.357 for the PDML area and 0.396 for the VIRM zone. The values ​​for the parameters of the consanguinity coefficient (Fis and Fit) were positive for the population and subpopulations, proving the existence of consanguinity. The value for the Fst was 0.042 among subpopulations defined as geographical areas (p<0.001), which suggests that the population analysed corresponds to two breed groups. This is supported by the analysis of principal components where there is evidence of a tendency of isolation among individuals for each geographical area. In conclusion, it is valid to say that the genetic diversity of the population of Colombian Creole Hair Sheep, compared to other sheep breeds worldwide, is high.